The Practice of Two-Phase Recommender System for Sporting Goods - Lo, Win-Tsung; Chang, Yue-Shan; Sheu, Ruey-Kai; Jung, JaiE. (Malaysian Journal of Computer Science, 2014)
Recommendation systems are majorly developed based on relationships of product features or between consumer attributes. Most of them need a lot of analysis of historical shopping transactions and statistical user or product features to come out good suggestions for consumers to make right decisions. However, it does not fit into the users’ shopping experiences for specialty stores of sporting goods. The characteristics of sporting goods specialty stores are less products and less volume of customers than other types of stores. It is hard for recommender systems to help users making the shopping decisions with limited product information and users’ historical shopping behaviors. It is the purpose of this paper to propose a two-phase recommendation technique based on the AHP methodology to improve the selling of sporting goods specialty stores. We also implemented a practice system for a specialty store selling badminton-related goods. The results show that it is easier for sporting goods stores to promote products, and help consumers to choose products based on their own features.